Tumorigenic 3T3 cells maintain an alkaline intracellular pH under physiological conditions. - Gillies, R J (1990)
One of the earliest events in the response of mammalian cells to mitogens is activation of Na+/H+ exchange, which increases intracellular pH (pHin) in the absence of HCO3- or at external pH values below 7.2. The proliferative response can be blocked by preventing the pHin increase; yet, the proliferative response cannot be stimulated by artificially raising pHin with weak bases or high medium pH. These observations support the hypothesis that optimal pHin is a necessary, but not sufficient, component of the proliferative-response sequence. This hypothesis has recently been challenged by the observation that transfection of NIH 3T3 cells with yeast H(+)-ATPase renders them tumorigenic. Although previous measurements indicated that these transfected cells maintain a higher pHin in the absence of HCO3-, whether H(+)-ATPase transfection raised the pHin under physiologically relevant conditions was not known. The current report shows that these transfected cells do maintain a higher pHin than control cells in the presence of HCO3-, supporting the possibility that elevated pHin is a proliferative trigger in situ. We also show that these cells are serum-independent for growth and that they glycolyze much more rapidly than phenotypically normal cells.